Main agricultural production projects implemented by ex-combatants from “Héctor Ramírez” rural settlement located in La Montañita, Colombia - Rojas Peña, Oscar Raul (2022)
This paper analyzed the importance of productive projects in the reintegration process of ex-combatants of the Revolutionary Armed Forces of Colombia (FARC), in the rural settlement “Héctor Ramírez” located in Caquetá, after the signing of the Colombian peace process in 2017. In this regard, the research was characterized by being a descriptive study as a qualitative approach, using the semi-structured interview as a data collection instrument applied to ex-combatants to recognize their expectations about the productive projects that they have been developing in the camp. It was found that ex-combatants reinvest the earnings received in productive projects to achieve, under their criteria, possibilities of growth and financial return for the long term. In addition, they hope that the Colombian government will support the improvement of the commercialization processes of the products generated in the different projects. In this way, the standards of well-being at the personal and community level will be improved.